The awareness and attitudes of male and female students at the Faculty of Basic Education towards the concept of plagiarism and the ethics of scientific research - al-Musawi, Hashemih Muhammad; Al-Qallaf, Bader Jassim (Journal of Educational and Psychological Sciences, 2018)
The remarkable activity of modern day authorship, publication and translation, combined with the technological advances of online media, enables unprecedented access to vast amounts of information. This in turn facilitates a greater opportunity for plagiarism, which makes it necessary to reassert the value of scientific ethics in dealing with the literature. Hence, this study aims to establish the extent of knowledge and adherence to research ethics among students in the College of Basic Education in Kuwait. The study uses a survey to focus on the students’ awareness of the concept of plagiarism, its types, driving factors, consequences, prevalence and methods of avoidance. The results identify not only a lack of awareness among the majority of students, but also frequent and repeated participation in plagiarism and its various forms. It is also evident that the students require support and guidance to avoid such practices in the future. This study finally proposes recommendations and suggestions to contain the problem of plagiarism and improve the standards of research and scientific duties of university affiliates in Kuwait.
Keywords: plagiarism; ethics of scientific research; College of Basic Education; Kuwait